Wynagrodzenie pracownika naukowego biorącego udział w realizacji filmu naukowego - Ślęzak, Piotr (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The scientific audiovisual work is a work, when the authors represent the facts and scientific theories , using light and sound as an artistic material. Due to the presence in works of this scientific layer, the representatives of science world appear in film crew besides representatives of typical film professions. They play different roles on film production. They can speak out on the screen or perform the role of so-called scientific consultants. The speech on screen can be a scientific work (similar to classic academic lecture). Film producer concludes agreements on audiovisual production with scientists, who perform on the screen. The role of scientist can come down also to a consultation for substantive correctness of verbal comment or either for comment translation correctness on audiovisual work it is possible both, the conclusion of agreement on audiovisual production or a separate agreement relative to “review” of verbal comment. In these agreements the sides foresee that the scientist receive the remuneration for participation in film production. The Author makes the assessment that the scientists are not film creators, therefore they do not receive additional remuneration for film distribution. For this reason the remuneration for participation in film production should be set up at the level, which would consider expected incomes from scientific audiovisual work exploitation.